Garden tools & equipment (Newton, 1995)
A collection of articles from "Fine Gardening" magazine which suggests the best tools for each gardening project and how to use them. It also contains a variety of useful gardening tips.
Keywords: Garden tools,Gardening,Dụng cụ làm vườn,Nghề làm vườn; Equipment and supplies,Cung cấp trang thiết bị